(untitled) (Asian Journal of Medical and Biological Research, 2022)
It is currently unknown how effective the COVID-19 vaccine is at preventing new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections among the general population. The study suggests that a safe and efficient vaccination against the COVID-19 could help manage this pandemic if widely distributed. The present study aimed to investigate the effectiveness of the ChAdOx1 nCoV-19 vaccine in between vaccinated and unvaccinated cohorts. A retrospective multicenter cohort study comprised 1244 COVID-19 positive patients enrolled in this study from three different hospitals among patients who had been appropriately vaccinated or not between April and June 2021. Data were collected by face-to-face survey, and clinical investigations were obtained by observation. Descriptive statistics and the Cox proportional hazard model of survival analysis were performed in the study. Among the participants, 69% of vaccinated cohorts did not require hospitalization, and 97% successfully recovered from the infection. In respect of age, compared with unvaccinated cohorts, the vaccine effectiveness varied from 81% to 92%. The ChAdOx1 nCoV-19 vaccine was more effective among those aged 60-69 years old and reduced 92% hazard of death than the unvaccinated group [HR ratio - 0.081(.036-.179), P=0.0001]. The study found the ChAdOx1 nCoV-19 vaccine is highly effective for receivers. The COVID-19 vaccination demonstrated a significant correlation with a reduced probability of disease severity, hospital admission rate, early recovery from illness, and mortality. Asian J. Med. Biol. Res. 2022, 8 (4), 251-263